(untitled) (Perner’s Contacts, 2014)
The article deals with the operational efficiency of large container vessels from the point of view of TEU unit costs. The main issue is the calculation of unit costs which is implemented into a model maritime transport route for two different type of container ships: Triple E class and Suezmax.